Luxury Brand Marketing Strategy - Taking Chanel as An Example - Zhang, Yujie (Transactions on Economics, Business and Management Research, 2024)
With the end of the epidemic, people’s consumption patterns and habits have changed a lot. Against this background, Chanel’s sales increased in 2023. There are many studies on Chanel’s marketing strategy. However, there are few studies on the reasons behind Chanel’s sales growth. The purpose of this article is to investigate the reasons for Chanel’s increased sales in 2023 from a marketing strategy perspective. This article utilizes brand extension theory, integrated marketing communication theory, customer relationship management theory, and case analysis to deeply analyze the reasons for Chanel’s sales growth. The results suggest that Chanel’s sales growth can be attributed to its unique design and innovation, with visual marketing being the key area for improvement. The second reason involves strong marketing and brand promotion, and Chanel must also engage in diversified marketing strategies. The third reason is effective customer relationship management, and Chanel needs to conduct customer segmentation on this basis. This study will provide a reference for other scholars who investigate Chanel’s sales and will help Chanel realize higher sales in the future.